Electrical and Optical Characterization of AlxGa1-xAs/GaAs P-n Junctions Grown via Liquid Phase Epitaxy - Laniog, J. N.; Bautista, K. M. A. N.; Patricio, M. G.; Sarmago, R. V.; Salvador, A. A. (Science Diliman: A Journal of Pure and Applied Sciences; Vol 13 No 2 (2001), 2012)
Excerpt The AlxGa1-xAs/GaAs heterostructure system is of prime importance for use in high-speed digital and electro-optic device applications. The compositional dependence of the bandgap energy of AlxGa1-xAs can be tailored to meet specific device requirements such as photon emission and detection. The 0.15% lattice parameter difference between GaAs and AlxGa1-xAs (0≤x≤0) at 300 K ensures that the density of interface states is kept to a level that would not affect device performance. These two properties of AlxGa1-xAs/GaAs alloy system make it one of the most technologically important semiconductors to date (Adachi, 1985).